2020
DOI: 10.3390/ijerph17155362
|View full text |Cite
|
Sign up to set email alerts
|

Human Papilloma Virus Infection and Vaccination: Pre-Post Intervention Analysis on Knowledge, Attitudes and Willingness to Vaccinate Among Preadolescents Attending Secondary Schools of Palermo, Sicily

Abstract: In recent years, vaccination coverage rates against Human Papilloma Virus (HPV) in Europe have shown a decreasing trend and remain below the required standard. The present study aims to assess knowledge and attitudes regarding HPV infection and vaccination among a representative sample of preadolescents of Palermo, Italy. A survey was carried out throughout two questionnaires, before and after carrying out an educational intervention scheduled during school hours. A total of 1702 students attending first-grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
15
0
3
Order By: Relevance
“…Ten-point Likert-type scales to measure the level of trust in particular vaccines and fear of vaccination were selected based on literature review, which indicated that they were successfully applied in various cross-sectional studies investigating the vaccine acceptance and perceived risk of vaccination [ 30 , 31 , 32 , 33 , 34 , 35 ]. The questionnaire was pre-tested by the researchers, including the professional vaccinologist (J.W.).…”
Section: Methodsmentioning
confidence: 99%
“…Ten-point Likert-type scales to measure the level of trust in particular vaccines and fear of vaccination were selected based on literature review, which indicated that they were successfully applied in various cross-sectional studies investigating the vaccine acceptance and perceived risk of vaccination [ 30 , 31 , 32 , 33 , 34 , 35 ]. The questionnaire was pre-tested by the researchers, including the professional vaccinologist (J.W.).…”
Section: Methodsmentioning
confidence: 99%
“…Given the size of the target population (defined as a group of fully vaccinated individuals in Poland at the time of the study), it was calculated using Cochran's formula [37] that at least 2401 eligible individuals should be surveyed to reach a margin level of 2% at the confidence level of 95%. Ten-point Likert-type scales to measure the level of vaccination fear and severity of side effects following the initial COVID-19 vaccination were chosen as they were successfully employed in various other cross-sectional investigations of vaccine hesitancy and attitudes [33,[38][39][40][41]. The scales' internal consistency reliability was determined with Cronbach's alpha and demonstrated good reliability of α = 0.82-0.93.…”
Section: Surveymentioning
confidence: 99%
“…The current HPV vaccination programs are mainly dedicated to preadolescents (age range 9-14 years) as primary targets, either through organized school-based vaccination plans or delivered through primary care services (including general practitioners, paediatricians, nurses, obstetrics, and gynaecologists). Moreover, according to the information provided by the Centers for Disease Control and Prevention (CDC), Advisory Committee on Immunization Practices (ACIP), HPV vaccination is also recommended for everyone by the age of 26 [38,39]. After ten years since the introduction of the vaccine and sixteen years of cervical cancer screening availability, a decrease in hospital admissions for CC and other HPV-related diseases was observed in several contexts [20,21].…”
Section: Primary Prevention: Hpv Vaccinationmentioning
confidence: 99%